Electrochemical characterisation of X10CrNi 18-8 steel in artificial plasma - J. Przondziono (Metalurgija, 2015)
Quality of applied guide wires conditions the course of treatment and its success to a great extent. In order to simulate conditions that can be found in blood vascular system samples were exposed to artificial blood plasma (T = 37 } 1 oC) for the time of 8 h. In order to obtain information regarding physical and chemical properties of modified surface of wire made of X10CrNi 18-8 steel, electrochemical impedance spectroscopy (EIS) test and tests of chemical composition of the surface layer X-ray photoelectron spectroscopy (XPS) were made. On the ground of performed EIS and XPS tests, favourable impact of steam sterilisation process on corrosion resistance of X10CrNi 18-8 steel was observed only for the case when chemical passivation was applied prior to sterilisation.